Toxicidade do cádmio em uma cadeia alimentar constituída por uma microalga (Scenedesmus quadricauda), um cladócero (Simocephalus serrulatus) e um peixe (Hyphessobrycon eques) - Souza, Jaqueline Pérola de (2012)
The effects of trace metals contamination in aquatic environments are of concern in the ecotoxicological point of view. In these environments the organisms are exposed to metals in the dissolved form and also through ingestion of contaminated food in the food chain. The phytoplanktonic organisms are the basis of food chains and are responsible for primary productivity. Zooplankton is a link between primary producers and higher trophic levels, such as fish. The exposure of these organisms to metals will cause changes in the physiology, affect productivity rates, and the balance and dynamics of aquatic communities. This study evaluated the effects of the metal cadmium (Cd) on an experimental freshwater food chain involving the algae Scenedesmus quadricauda, a cladoceran daphinidae, Simocephalus serrulatus, and the fish Hyphessobrycon eques. Cultures of S. quadricauda in exponential phase growth were exposed to 1.6x10-9; 3.2x10-8; 6.7x10-8; 1.6x10-7 and 1.3x10-6 mol L-1 of total dissolved Cd for 96 h. During exposure chlorophyll "a", population growth, coenobia size, and dry biomass were evaluated. Then the contaminated algae were given as food to the zooplankton S. serrulatus during the complete life cycle of the organisms in the concentration range of 3.8x10-14 to 5.9x10-12 g Cd cell-1. During the exposure the embryonic development time, age at first reproduction, time for egg production, generation time, longevity, fertility rates, feeding rates, secondary production, and recovery of the animals were evaluated. Then the cladocerans reared with Cd contaminated algae were used as food for the fish H. eques duruing a period of seven days. At the end of this exposure, we evaluated the histological structure of gills and liver, and the fresh weight of the animals. In S. quadricauda, there were damages on the chlorophyll content, and in the population growth at high concentrations of the metal. In the cladocerans were detected increase of the embryonic development time, age at first reproduction, and generation time, whereas a decrease of the longevity, fertility rates, feeding rates, and secondary production. The rate of secondary production showed recovery after removal the contaminated food. The histological patterns of gills and liver, as well as the fresh weight of the fish were not affected by the Cd exposure tested through the food chain considering the exposure period and concentrations tested. The results indicated that food can be considered an important vehicle in the Cd transfer from phytoplankton to zooplankton in aquatic food webs. Cd has a high potential for toxicity, impacting the producers and primary consumers. However, no Cd effects to the fish, the third trophic level, were detected. These studies are of great importance for understanding Cd behavior in aquatic environments, as well as its toxicity to the organisms. The understanding of these aspects contributes to adaptation strategies for the conservation of aquatic ecosystems in situations of contamination.